Molecular Pharmacology of Kidney and Inner Ear CLC-K Chloride Channels - Gradogna, Antonella; Pusch, Michael (Frontiers in Pharmacology, 2010)
CLC-K channels belong to the CLC gene family, which comprises both Cl- channels and Cl-/H+ antiporters. They form homodimers which additionally co-assemble with the small protein barttin. In the kidney, they are involved in NaCl reabsorption ; in the inner ear they are important for endolymph production. Mutations in CLC-Kb lead to renal salt loss (Bartter’s syndrome); mutations in barttin lead additionally to deafness. CLC-K channels are interesting potential drug targets. CLC-K channel blockers have potential as alternative diuretics, whereas CLC-K activators could be used for the treatment of patients with Bartter’s syndrome. Several small organic acids inhibit CLC-K channels from the outside by binding to a site in the external vestibule of the ion conducting pore. Benzofuran derivatives with affinities better than 10 µM have been discovered. Niflumic acid (NFA) exhibits a complex interaction with CLC-K channels. Below ~ 1 mM, NFA activates CLC-Ka, whereas at higher concentrations NFA inhibits channel activity. The co-planarity of the rings of the NFA molecule is essential for its activating action. Mutagenesis has led to the identification of potential regions of the channel that interact with NFA. CLC-K channels are also modulated by pH and [Ca2+]ext. The inhibition at low pH has been shown to be mediated by a His-residue at the beginning of helix Q, the penultimate transmembrane helix. Two acidic residues from opposite subunits form two symmetrically related intersubunit Ca2+ binding sites, whose occupation increases channel activity. The relatively high affinity CLC-K blockers may already serve as leads for the development of useful drugs. On the other hand, the CLC-K potentiator NFA has a quite low affinity, and, being a non-steroidal anti-inflammatory drug, can be expected to exert significant side effects. More specific and more potent activators will be needed and it will be important to understand the molecular mechanisms that underlie NFA activation.